Parallel Imaging Microfluidic Cytometer - Ehrlich, Daniel J. (2011)
By adding an additional degree of freedom from multichannel flow, the parallel microfluidic cytometer (PMC) combines some of the best features of flow cytometry (FACS) and microscope-based high-content screening (HCS). The PMC (i) lends itself to fast processing of large numbers of samples, (ii) adds a 1-D imaging capability for intracellular localization assays (HCS), (iii) has a high rare-cell sensitivity and, (iv) has an unusual capability for time-synchronized sampling. An inability to practically handle large sample numbers has restricted applications of conventional flow cytometers and microscopes in combinatorial cell assays, network biology, and drug discovery. The PMC promises to relieve a bottleneck in these previously constrained applications. The PMC may also be a powerful tool for finding rare primary cells in the clinic. The multichannel architecture of current PMC prototypes allows 384 unique samples for a cell-based screen to be read out in approximately 6–10 minutes, about 30-times the speed of most current FACS systems. In 1-D intracellular imaging, the PMC can obtain protein localization using HCS marker strategies at many times the sample throughput of CCD-based microscopes or CCD-based single-channel flow cytometers. The PMC also permits the signal integration time to be varied over a larger range than is practical in conventional flow cytometers. The signal-to-noise advantages are useful, for example, in counting rare positive cells in the most difficult early stages of genome-wide screening. We review the status of parallel microfluidic cytometry and discuss some of the directions the new technology may take.